Magnetic resonance imaging in infections of the central nervous system. - Davidson, H D; Steiner, R E (American Journal of Neuroradiology, 1985)
The magnetic resonance (MR) images in 24 patients with infections of the central nervous system (CNS) were reviewed, and the use of a paramagnetic contrast agent (Gd-DTPA) in two cases is reported. The clinical diagnoses in the patients, aged neonate to 71 years old, comprised meningitis, meningitis and subdural empyema, meningoencephalitis, encephalitis, and single or multiple cerebral abscesses. A new sign of CNS infection, the pial-ependymal line, is described. Other consequences of infection, such as atrophy, delayed myelination, periventricular cerebrospinal fluid extravasation, changes in T1 and T2, and mass effect, are reported and discussed. MR imaging may have a significant application in the study of CNS infections because of the importance of early diagnosis in instituting effective treatment.